Mood disorders in higher education in Flanders during the 2nd and 3rd COVID-19 wave: Prevalence and help-seeking: Findings from the Flemish College Surveys (FLeCS). (March 2023) - Bootsma, Erik; Jansen, Leontien; Kiekens, Glenn; Voorpoels, Wouter; Mortier, Philippe; Proost, Sebastian; vande Poel, Ilse; Jacobs, Karen; Demyttenaere, Koen; Alonso, Jordi; Kessler, Ronald C.; Cuijpers, Pim; et al.
Abstract: To examine the prevalence of 12-month mood disorders and receipt of mental health treatment among a volunteer sample of higher education students during the 2nd and 3rd COVID-19 wave in the Flanders region. Web-based self-report surveys were obtained from 9101 students in higher education in the Flemish College Surveys (FLeCS) in Flanders, Belgium. As part of the World Health Organization's World Mental Health–International College Student Initiative, we screened for 12-month mood disorders (major depressive episode (MDE), mania/hypomania), and service use. We used poststratification weights to generate population-representative data on key socio-demographic characteristics. 50.6% of the respondents screened positive for 12-month mood disorders (46.8% MDE, of which 22.9% with very severe impact). Use of services was very low, with estimates of 35.4% for MDE, 31.7% for mania, and 25.5% for hypomania. Even among students with very severe disorders, treatment rates were never higher than 48.3%. Most common barriers for not using services were: the preference to handle the problem alone (83.4%) and not knowing where to seek professional help (79.8%). We found a high unmet need for mood problems among college students; though caution is needed in interpreting these findings given the volunteer nature of the sample. A reallocation of treatment resources for higher education students should be considered, particulary services that focus on innovative, low-threshold, and scalable interventions.